Spracheinstellungen und Identitätskonstruktion. Eine gesprächsanalytische Untersuchung sprachbiographischer Interviews mit Deutsch-Vietnamesen - König, Katharina (Empirische Linguistik / Empirical Linguistics, 2014)
This study examines statements about language setting expressed by bilingually raised Germans of Vietnamese origin during language biographical interviews in search of specific conversational features. A further focus of the research is on the linguistic construction of different language spaces in which the interviewees position themselves as multilingual individuals.